Symptoms at disease onset predict prognosis in COVID-19 disease. Issue 1 (31st December 2022) - Zhou, Aiyuan; Song, Qing; Peng, Yating; Liao, Xin; Huang, Peng; Liu, Wenlong; Xiang, Zhi; Liu, Qimi; Jiang, Mingyan; Xiang, Xudong; Deng, Dingding; Chen, Ping
ABSTRACT: The main clinical manifestations of coronavirus disease 2019 (COVID-19) onset are respiratory symptoms, including cough, sputum, and dyspnea. However, a significant proportion of patients initially manifested non-respiratory symptoms, such as fever, myalgia, and diarrhea. Here, we compared the different characteristics and outcomes between the patients with respiratory symptoms and non-respiratory symptoms at illness onset. The patients admitted to the respiratory departments from eight hospitals in Hunan and Guangxi Province with nucleic acid-positive severe acute respiratory syndrome coronavirus (SARS-CoV-2) were recruited. Epidemiological information, clinical manifestations, laboratory findings, and radiological characteristics, treatment regimens, and outcomes data were recorded and analyzed. The median age of the recruited 541 subjects was 43 years (IQR, 33–55). Of the 541 subjects, 404 (74.5%) subjects had initial symptom that were respiratory, while 137 (25.5%) subjects had non-respiratory symptoms. Respiratory COVID-19 subjects had more secondary bacterial infections (8.7% vs 0.0%, P < 0.001), needed the intensive care unit more (9.7% vs 2.2%, P = 0.005), non-invasive ventilation more (7.2% vs 1.5%, P = 0.004), developed ARDS more (11.4% vs 2.2%, P = 0.001) and needed longer time to recover (18.5 vs 16.7 days, P = 0.003) compared to predominately non-respiratory COVID-19 subjects. The multivariate model showed that age (OR = 1.04, P = 0.01), dyspnea (OR = 4.91, P < 0.001) and secondary bacterial infection (OR = 19.8, P < 0.001) were independently associated with development of ARDS among COVID-19 patients. We identify COVID-19 subjects with dyspnea at disease onset who have a worse prognosis. We also demonstrate age and secondary bacterial infections to be independently associated with ARDS development in subjects with COVID-19. ABBREVIATIONS : COVID-19: Coronavirus disease 2019; ARDS: acute respiratory distress syndrome; IQR: interquartile range; ICU: intensive care unit; CDC: Chinese Center for Disease Control and Prevention.